2014
DOI: 10.1097/pec.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Anterior Arch of Atlas After Minor Trauma of the Immature Spine Postlaminectomy

Abstract: Torticollis is a common complaint in the pediatric emergency department. Here, we report what we believe to be the first example in a young child of a fracture of the anterior arch of the atlas associated with an acquired, postsurgical defect of the posterior arch. A brief review of pediatric cervical spine injuries and fractures is presented. Atlas laminectomy may predispose patients to isolated atlas fractures even with minor trauma. Those fractures, however, are stable and treated by hard cervical orthosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Although it is reasonable to keep radiation exposure as low as possible, further investigations should always be considered in the case of unremarkable X-rays with persisting neck pain and limited range of neck motion 23. Our patient did not demonstrate any prevertebral soft tissue swelling, an indirect sign of a fracture of the C-spine, on plain X-ray images 24. Therefore, we decided to perform an MRI of the C-spine in accordance with the suggestion of Judd et al 25 to further assess the integrity of the atlantal ligament.…”
Section: Discussionmentioning
confidence: 82%
“…Although it is reasonable to keep radiation exposure as low as possible, further investigations should always be considered in the case of unremarkable X-rays with persisting neck pain and limited range of neck motion 23. Our patient did not demonstrate any prevertebral soft tissue swelling, an indirect sign of a fracture of the C-spine, on plain X-ray images 24. Therefore, we decided to perform an MRI of the C-spine in accordance with the suggestion of Judd et al 25 to further assess the integrity of the atlantal ligament.…”
Section: Discussionmentioning
confidence: 82%
“…It is not easy to clearly define treatment for anterior arch fracture of the atlas. Two of our cases (case 1 and case 3) and one pediatric case in the literature (case 7 in Table 3) [9] were treated conservatively. Our two conservatively treated cases did not demonstrate bony union, although the patients remained asymptomatic for at least 15 and 30 months, respectively, after the fracture.…”
Section: Discussionmentioning
confidence: 94%
“…(2) O'Shaughnessy et al 5 reported 2 cases of C1 laminectomies for Chiari malformation type I as follows: an 18-year-old female patient who was treated with a C1-C2 fusion and a 49-year-old female patient who was treated with bone morphogenetic protein (BMP) 2 through a standard anterior cervical incision, followed by the placement of an orthotic halo for 3 months. (3) Baghdassarian et al 6 reported a case of a 4-year-old female patient who underwent a C1 laminectomy for the removal of cerebellar astrocytoma 4 months earlier. She underwent brace therapy using a Miami-J orthosis, thereby achieving bone union.…”
Section: Discussionmentioning
confidence: 99%